KETAHANAN LIMA JENIS KAYU ASAL CIAMIS TERHADAP SEBELAS STRAIN JAMUR PELAPUK - Sihati Suprapti; Djarwanto (Jurnal Penelitian Hasil Hutan, 2014)
Fungal resistance of five wood species from Ciamis: langkaled (Litsea roxburghii Hassk.), cangkring (Erythrina fusca Lour.), kayu putih (Melaleuca cajuputi Powell), ki tanab (Zanthoxylum rhetsa D.C.), and burun leueur (Sterculia cordata Blume), was observed using Kolle-Halls method. Wood samples of inner and outer parts of the log were prepared from three trees of every species. Wood samples were tested against eleven strain of decaying fungi. The results show that langkaled and ki tanab woods are classified as resistant (class III), while cangkring, kayu putih and burun leueur woods fall into not-resistant (class IV). In general, the weight loss of samples taken from outer part is greater than those taken from the inner part of the log. It indicates that wood samples taken from outer part (not resistant, class IV) is less resistance than the inner part (moderately resistant, class III). There were also resistant variations between trees. In those five wood species, for example, the first tree (P-I) belong to class III, however the second and third tree (P-II and P-III) falls in to class IV. The highest weight loss was recorded in a wood sample of P-I of cangkring, which was exposed into Pycnoporus sanguineus HHBI-324. The wood fungi decaying capability from the highest to the lowest are P. sanguineus HHBI-324, P. sanguineus HHBI-348, Polyporus sp. HHBI-209, Trametes sp., Polyporus sp. HHBI-371, Schizophyllum commune, Chaetomium globosum, P. sanguineus HHBI-345, P. sanguineus HHBI-8149, Xylaria spinosis, and Dacryporus spathularia.